Modern Slavery and Forced Labour: An Overview of International Law, the Malaysian Law and Islamic Law Perspectives - Hendun Abd Rahman Shah (AHKAM : Jurnal Ilmu Syariah, 2021)
The paper aims to provide an overview of modern slavery and forced labour under international, Malaysian and Islamic law perspectives. It employs doctrinal methods which mainly focus on library-based research through legal analysis and review of past works, as well as the historical and explanatory method that help explain the views of commentators and scholars in international and Islamic law. It then connects ideas to understand the issue in the local context. This paper concludes that there is a lack of a clear definition of modern slavery universally, which makes it difficult to identify whether the exploitation of the workers, is amounting to merely a violation of rights or to some extent is amounting to slavery or forced labour or trafficking of persons as demarcated by either International law or the Malaysian law. Nevertheless, Islamic law has not given much emphasis on definition, rather it provides remedy and guidelines in protecting workers from oppression and slavery such as regulating the relationship between the employer and the worker according to the precise legal criteria to guarantee fulfilment of rights and non-aggression so that labour does not turn into a new arena of modern slavery.   Abstrak: Paper ini bertujuan untuk memberikan gambaran tentang perbudakan modern dan kerja paksa di bawah perspektif hukum internasional, hukum Malaysia dan hukum Islam. Penelitian ini menggunakan metode doktrinal melalui analisis hukum dan tinjauan karya-karya masa lalu, serta metode sejarah yang membantu menjelaskan pandangan para komentator dan sarjana dalam hukum internasional dan hukum Islam yang dihubungkan dengan ide-ide untuk memahami masalah dalam konteks lokal. Penelitian ini menyimpulkan bahwa ada kekurangan definisi yang jelas tentang perbudakan modern secara universal, yang membuat sulit untuk mengidentifikasi apakah eksploitasi pekerja, hanya merupakan pelanggaran hak atau sampai batas tertentu merupakan perbudakan atau kerja paksa atau perdagangan orang sebagaimana diatur oleh hukum Internasional atau hukum Malaysia. Namun demikian, hukum Islam belum banyak memberikan penekanan pada definisi, melainkan memberikan perbaikan dan pedoman dalam melindungi pekerja dari penindasan dan perbudakan, seperti mengatur hubungan antara majikan dan pekerja sesuai dengan kriteria hukum yang tepat untuk menjamin pemenuhan hak sehingga tenaga kerja tidak berubah selalu menjadi arena perbudakan modern.